Pengaruh Literasi Digital dan Orientasi Kewirausahaan Terhadap Kinerja Usaha Di Sentra Industri Rajut Binong Jati Bandung - Kartika, Dewi; Ratnamiasih, Ina (Brainy: Jurnal Riset Mahasiswa, 2023)
This study aimed to determine the effect of Digital Literacy and Entrepreneurial Orientation on Business Performance  both simultaneously and partially at the Binong Jati Knitting Industrial Center Bandung. The research method used was descriptive and verification methods with a sample size of 201 respondents. Meanwhile, the data collection techniques used in this research are observation, interviews and distributing questionnaires. The analytical methods used include multiple linear regression, multiple correlation and coefficient of determination. The results of this research show that there is a positive and significant influence simultaneously and partially. Simultaneously the effect of Digital Literacy  and Entrepreneurial Orientation on Business Performance) is 71,6%, while partially Digital Literacy  has an effect on Business Performance has an effect of 53,2% and Entrepreneurial Orientation influence on Business Performance gives an effect of 18,4% it can be concluded that Digital Literacy  and Entrepreneurial Orientation  have a significant influence on Business Performance  at Binong Jati Knitting Industrial Center Bandung.